(untitled) (World Bulletin of Social Sciences, 2026)
Digitalization is becoming a major driver of change in vocational education, especially in technical higher education institutions. This conceptual study proposes a comprehensive methodological framework aimed at improving digitalization in vocational education. The study reviews existing pedagogical and technological approaches and identifies key challenges. It also synthesizes them into a structured model with four stages: diagnostic analysis, digital competence development, technological integration, and continuous monitoring and evaluation. The proposed framework emphasizes adaptive learning tools, learning management systems, simulation technologies, and analytics-based assessment. Unlike bibliometric or empirical studies, this article aims to provide a theoretical and methodological framework oriented towards future practical application